Effect of enhanced CO2 atmospheric concentration on rice and weedy rice - Balbinot, Andrisa (2020)
Global climate change causes stresses that can limit crop productivity and threaten food production in the future. Increased production implies an increase in the demand for water, with irrigation being the activity that most uses fresh water today. The culture of rice represents an important staple food and effects of the increase in atmospheric CO2 atmospheric can affect development and production, in addition to affecting weedy rice, the most important weed in flooding rice system. Therefore, the present research aimed to evaluate the effect of increasing CO2 atmospheric associated with different water regimes on rice and weedy rice. For this, experiments were carried out to evaluate development and water use efficiently in rice crop and also, quantify the total concentration of arsenic and cadmium in grains; the effects in weedy rice growth, development, seed shattering and longevity of seed bank; the gene expression to genes to be related to involve on seed shattering in rice, and to evaluated on the quality of grains and physicochemical proprieties in rice and red rice. The results allowed indicated that increase in CO2 affects the growth, development and water use efficiency in rice. In addition, in the assessment of total arsenic, intermittent regime decreased the absorption of the element. Considering the studies development with weedy rice, the effect of increase CO2 was observed for growth and development, in addition to increasing the seed shattering and seed viability at seedbank. In addition, gene expression demonstrated that the genes OsCPL1, qSH1, SHAT1, OsXTH8, OSH15 and SH5 are affected by the increase in CO2, making the characteristic more complex because involver several metabolic pathways. Contemplating the grain yield analysis, white rice had a decrease in head rice yield in high CO2, in addition an increase in the chalkiness area and a decrease in crude protein, with changes in cooking parameters. These results contribute to characterization of increase CO2 in rice crop, being the basis for future studies, which continue in search to elucidate the effects of climate change in agriculture, assisting in the planning of the adoption of sustainable management, in order to minimize the negative effects.